Sedimentary rock hosted copper mineralization in the Neoproterozoic Redstone Copperbelt, Northwest Territories, Canada ... - Milton, Jack Edward (University of British Columbia, 2015)
Physical-chemical fluid evolution, timing of fluid-migration and driving forces for fluid-flow are factors that fundamentally control the mass transport that leads to the formation of sedimentary rock hosted copper deposits. This thesis constrains these factors for Kupferschiefer-type mineralization in a sequence of Neoproterozoic rocks of the Redstone Copperbelt, Mackenzie Mountains, Northwest Territories, Canada. Stratiform copper mineralization is located in rift-basins that formed during the break-up of the supercontinent Rodinia within a period of Earth’s history that witnessed evolution of Precambrian life and dramatic climate changes associated with the Snowball Earth glaciations. A U-Pb zircon date is presented, constraining the eruption of a marker unit within the Neoproterozoic sequence that heralded the prolonged period of rifting that led to supercontinent fragmentation. The age also constrains the deposition of the host rocks for stratiform copper mineralization. Dating monazite grains ...